2010
DOI: 10.1002/jcb.22642
|View full text |Cite
|
Sign up to set email alerts
|

Beclin 1 self‐association is independent of autophagy induction by amino acid deprivation and rapamycin treatment

Abstract: Autophagy, a process of self-digestion of cellular constituents, regulates the balance between protein synthesis and protein degradation. Beclin 1 represents an important component of the autophagic machinery. It interacts with proteins that positively regulate autophagy, such as Vps34, UVRAG, and Ambra1, as well as with anti-apoptotic proteins such as Bcl-2 via its BH3-like domain to negatively regulate autophagy. Thus, Beclin 1 interactions with several proteins may regulate autophagy. To identify novel Becl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…Previous studies and our experiments demonstrate that Beclin 1 forms a dimer in vitro and in vivo as mediated by its CC domain1819203132. Here we show that the crystal structure of Beclin 1 CC domain is an antiparallel dimeric CC with the unexpected characteristic of containing a series of 'imperfect' a - d' pairings at its dimer interface.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Previous studies and our experiments demonstrate that Beclin 1 forms a dimer in vitro and in vivo as mediated by its CC domain1819203132. Here we show that the crystal structure of Beclin 1 CC domain is an antiparallel dimeric CC with the unexpected characteristic of containing a series of 'imperfect' a - d' pairings at its dimer interface.…”
Section: Discussionsupporting
confidence: 63%
“…We propose that a fraction of intracellular Beclin 1 exists in homodimer3132, particularly considering that both Atg14L- and UVRAG-containing Beclin 1–VPS34 complexes have been detected even though the Beclin 1–UVRAG complex has stronger affinity; however, the biological significance of the homodimeric Beclin 1 is unclear. It is tempting to propose that homodimeric Beclin 1, perhaps as a reserve pool, remain inactive; on autophagy induction or related signals, Beclin 1 can be triggered to undergo transition from inactive homodimer to heterodimeric Beclin 1–Atg14L/UVRAG formation that may be correlated with enhanced lipid kinase activity of VPS34 to promote autophagy.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, it is likely that this FHD trimer represents alternate FHD structure and oligomerization, in BECN1 states accessed while performing other biological functions. Notably, regions N-terminal to the CCD have been implicated in homo-oligomerization in other studies (71, 75), and it has been shown that the levels of homo-oligomerized BECN1 molecules in cells are not affected by induction of autophagy and association with the other core components of the PI3KC3 complex (75). Lastly, it is tempting to speculate that the sulfate-binding site created by the formation of this trimer may represent a site of interaction with a phosphorylated partner.…”
Section: Discussionmentioning
confidence: 94%
“…The BECN1 CCD, which is well conserved amongst homologs (Figure 1), has been shown to be sufficient for self-interaction in cells (61, 62). BECN1 homo-oligomers were detected in mammalian cells via co-immunoprecipitation (CoIP) and immuno-blotting, even during starvation and rapamycin induced autophagy (62).…”
Section: Discussionmentioning
confidence: 99%